Assessment of Medical Waste Management Practices (Derna Academy Journal for Applied Sciences, 2026)
Background: Medical waste management is a critical global concern due to its potential environmental and public health risks. In Tarhuna City, Libya, the lack of comprehensive studies on medical waste management has led to inadequate practices and limited awareness.  Aim of study: This study evaluates the current state of medical waste management in 23 public and private healthcare institutions in Tarhuna, focusing on waste generation, segregation, treatment, and disposal practices. Methodology: A mixed-methods approach, including questionnaires, interviews, and observations, was employed to gather data from 109 healthcare workers. Results: Findings reveal significant gaps in training, waste segregation, and adherence to safety protocols, with improper disposal methods posing risks to both workers and the community.  The study highlights the urgent need for improved infrastructure, training programs, and regulatory enforcement. Recommendations include raising awareness, adopting modern waste treatment technologies, and establishing a dedicated medical waste landfill.  Conclusions: This research contributes to the limited literature on medical waste management in Libya and provides actionable insights for policymakers and healthcare administrators.